Spatial distribution of tuberculosis in indigenous and non-indigenous populations in the state of Pará, Brazil, 2005-2013 - Bárbara Lopes Paiva; Jéssica Quelé Azeredo; Laura Maria Vidal Nogueira; Bruno de Oliveira Santos; Ivaneide Leal Ataide Rodrigues; Marcandra Nogueira de Almeida Santos (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To analyze the incidence of tuberculosis in indigenous and non-indigenous residents in the state of Pará from 2005-2013. Method: An ecological study was performed with data from SINAN, stratified for the 13 existing Regional Health Centers in Pará. The tuberculosis incidence rates were calculated for indigenous and non-indigenous populations in the 13 regions and maps were prepared to visualize the magnitude of the occurrence of tuberculosis. Results: Significant differences in the incidence of tuberculosis were found among non-indigenous and indigenous populations, reaching 7,812/100,000 inhabitants and 118/100,000 inhabitants respectively. Conclusion: Tuberculosis was distributed heterogeneously among the indigenous and non-indigenous populations. Moreover, it was possible to identify areas with high risk for this disease. It is important to note that knowledge about priority areas for tuberculosis control can help health service management to improve indicators that assess this disease and to develop different policies for indigenous peoples.